WACANA TUKAR PERAN RUMAH TANGGA DALAM KANAL YOUTUBE WOMANTALK - Ningrat, Leny Wahyu; Abrian, Rizky (PRASI, 2024)
The phenomenon of changing roles in the household often occurs today, where women are busy working, while men take care of the house. This condition can give rise to family conflict, because it is contrary to natural norms which should be, namely that the husband earns a living and the wife takes care of the house. However, even though quite a lot of people have experienced an exchange of roles in the household. This phenomenon is still considered taboo, especially by Indonesian society. Therefore, this research was conducted to explore the position of women seen from the perspective of the subject and object as well as when seen from the reader's position. Placed in the discourse on the video on the Womantalk YouTube channel entitled "Shifting Household Roles, the Phenomenon of Role Exchange in the Household." Using Sara Mills' critical discourse analysis theory, namely by looking at the text from the perspective of subject-object and writer-reader. The research results show that the phenomenon of changing roles in the household is not a problem, and can even be a solution for couples who need it. Keywords : Discourse analysis, gender, household, Sara Mills, role switching. ABSTRAK Fenomena pertukaran peran dalam rumah tangga saat ini kerap kali terjadi, di mana perempuan sibuk bekerja, sedangkan lelaki mengurus rumah. Kondisi ini dapat menimbulkan adanya konflik keluarga, karena bertentangan dengan norma kodrat yang semestinya, yakni suami mencari nafkah dan istri mengurus rumah. Namun, meskipun sudah cukup banyak yang mengalami pertukaran peran di dalam rumah tangga. Fenomena ini masih dianggap tabu, terutama oleh masyarakat Indonesia. Oleh karena itu, penelitian ini dilakukan untuk mengeksplorasi kedudukan perempuan dilihat dari sudut pandang subjek dan objek serta jika dilihat dari posisi pembaca ditempatkan dalam wacana pada video di kanal Youtube Womantalk bertajuk “Household Role-Shifting, Fenomena Pertukaran Peran di Rumah Tangga.” Menggunakan teori analisis wacana kritis Sara Mills, yakni dengan melihat teks dari perspektif subjek-objek dan penulis-pembaca. Hasil penelitian menunjukkan bahwa fenomena pertukaran peran dalam rumah tangga bukanlah masalah, bahkan dapat menjadi solusi bagi pasangan yang membutuhkan.